Nurse reported quality of care: A measure of hospital quality - McHugh, Matthew D.; Stimpfel, Amy Witkoski (Research in nursing & health, 2012)
As the primary providers of round‐the‐clock bedside care, nurses are well positioned to report on hospital quality of care. Researchers have not examined how nurses' reports of quality correspond with standard process or outcomes measures of quality. We assess the validity of evaluating hospital quality by aggregating hospital nurses' responses to a single item that asks them to report on quality of care. We found that a 10% increment in the proportion of nurses reporting excellent quality of care was associated with lower odds of mortality and failure to rescue; greater patient satisfaction; and higher composite process of care scores for acute myocardial infarction, pneumonia, and surgical patients. Nurse reported quality of care is a useful indicator of hospital performance. © 2012 Wiley Periodicals, Inc. Res Nurs Health 35:566–575, 2012